Development of a lateral flow device for in‐field detection and evaluation of PCR‐based diagnostic methods for Xanthomonas campestris pv. musacearum, the causal agent of banana xanthomonas wilt. (2nd October 2014) - Hodgetts, J.; Karamura, G.; Johnson, G.; Hall, J.; Perkins, K.; Beed, F.; Nakato, V.; Grant, M.; Studholme, D. J.; Boonham, N.; Smith, J.
<x xml:space="preserve">Abstract</x> Xanthomonas campestris pv. musacearum (Xcm) is the causal agent of banana xanthomonas wilt, a major threat to banana production in eastern and central Africa. The pathogen is present in very high levels within infected plants and can be transmitted by a broad range of mechanisms; therefore early specific detection is vital for effective disease management. In this study, a polyclonal antibody (pAb) was developed and deployed in a lateral flow device (LFD) format to allow rapid in‐field detection of Xcm. Published Xcm PCR assays were also independently assessed: only two assays gave specific amplification of Xcm, whilst others cross‐reacted with non‐target Xanthomonas species. Pure cultures of Xcm were used to immunize a rabbit, the IgG antibodies purified from the serum and the resulting polyclonal antibodies tested using ELISA and LFD. Testing against a wide range of bacterial species showed the pAb detected all strains of Xcm, representing isolates from seven countries and the known genetic diversity of Xcm. The pAb also detected the closely related Xanthomonas axonopodis pv. vasculorum (Xav), primarily a sugarcane pathogen. Detection was successful in both naturally and experimentally infected banana plants, and the LFD limit of detection was 105 cells mL−1. Whilst the pAb is not fully specific for Xcm, Xav has never been found in banana. Therefore the LFD can be used as a first‐line screening tool to detect Xcm in the field. Testing by LFD requires no equipment, can be performed by non‐scientists and is cost‐effective. Therefore this LFD provides a vital tool to aid in the management and control of Xcm.